Contrastive Analysis Of Idiom Translation: Literal vs. DeepL in Adele’s Song “Someone Like You” Into Indonesian - Yuni Maria Manullang; Masta Artani Damanik; Diane Sarima Lestari Simbolon; Sarah Nasrani Gea; Poster Sagala (Merwinspy Publisher, 2025)
This study investigates the challenges and strategies involved in translating English idioms into Indonesian, with a particular focus on Adele's song